2021
DOI: 10.21776/ub.jam.2021.019.02.11
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Performance of Manufacturing Companies in Idx and Some Factors That Influence

Abstract: This study aims to examine some factors affecting the financial performance of manufacturing companies in the Indonesia Stock Exchange (IDX). This research uses data on the financial statements of 20 manufacturing companies listed on IDX in the period 20132017 and carried out share distribution facilities for their employees. This research model is a panel regression model done by testing the common effect model, fixed-effect model, and random effect model. Based on the Chow test and Hausman test, it is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Financial Performance. Ichsan et al [13] states that Financial Performance is an important goal carried out by company managers for the future survival of the company. Financial performance pays attention to how the company's ability to achieve financial results as the main goal planned through expected output.…”
Section: Financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Financial Performance. Ichsan et al [13] states that Financial Performance is an important goal carried out by company managers for the future survival of the company. Financial performance pays attention to how the company's ability to achieve financial results as the main goal planned through expected output.…”
Section: Financial Performancementioning
confidence: 99%
“…Financial performance is measured using a Return on Asset (ROA) proxy. ROA utilizes company assets to measure the effectiveness of the company in building some profits [13].…”
Section: Financial Performancementioning
confidence: 99%
“…The Nairobi Influence Between 2007 and 2011, empirical research shown that CSR had no effect on the financial success of a firm. Researchers are encouraged to employ other study factors that might mitigate the association between GCG and CSR and a company's financial success due to the variability of the results of prior studies (Clarke, T., Lindorff, M., Jonson, 2013;Hopkins & Hopkins, 1997;Ichsan et al, 2021;Juita et al, 2021;Tripalupi & Anggahegari, 2020). The authors intend in reviewing the effect of GCG and CSR on financial performance by including earnings management as a mediating variable.…”
Section: Introduction *mentioning
confidence: 99%
“…Das and Swain (Ichsan et al, 2021) argued that there is no correlation between financial leverage and profitability. Rajverma (2019) revealed that there has a relationship between capital structure and profitability.…”
Section: Introduction *mentioning
confidence: 99%